2018
DOI: 10.1186/s12974-018-1329-8
|View full text |Cite
|
Sign up to set email alerts
|

Distinct contributions of hyperglycemia and high-fat feeding in metabolic syndrome-induced neuroinflammation

Abstract: BackgroundHigh-fat feeding and hyperglycemia, key risk factors for the development of metabolic syndrome (MetS), are emerging to associate with increased risk of developing dementia and cognitive decline. Despite this, clinical and experimental studies have yet to elucidate the specific contributions of either high-fat feeding or hyperglycemia to potential neuroinflammatory components. In this study, we delineate these individual components of MetS in the development of neuroinflammation.MethodsMale C57Bl/6 J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 49 publications
4
43
0
Order By: Relevance
“…Several reviews have summarised common features of animal models of diabetic cardiomyopathy (Hsueh et al, 2007; Bugger and Abel, 2009), and the Diabetic Complications Consortium provides validation criteria for animal studies of diabetes-induced complications. More recently, several laboratories have devised protocols that use a dietary intervention superimposed on the pancreatic toxin, STZ, to induce T2DM (Barrière et al, 2018; Wanrooy et al, 2018). This model exhibits diastolic dysfunction comparable to the db/db mouse but with a milder systemic phenotype, more closely resembling the progression of systemic metabolic changes observed in humans with T2DM, including progressive gains in body weight and fat mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews have summarised common features of animal models of diabetic cardiomyopathy (Hsueh et al, 2007; Bugger and Abel, 2009), and the Diabetic Complications Consortium provides validation criteria for animal studies of diabetes-induced complications. More recently, several laboratories have devised protocols that use a dietary intervention superimposed on the pancreatic toxin, STZ, to induce T2DM (Barrière et al, 2018; Wanrooy et al, 2018). This model exhibits diastolic dysfunction comparable to the db/db mouse but with a milder systemic phenotype, more closely resembling the progression of systemic metabolic changes observed in humans with T2DM, including progressive gains in body weight and fat mass.…”
Section: Discussionmentioning
confidence: 99%
“…Although this model does not mimic the more clinically prevalent T2DM, the STZ model avoids confounding factors including obesity and impaired leptin signalling which need to be taken into account in common genetic models of T2DM, including spontaneously diabetic db/db and ob/ob mice. Recently, there has been an emergence of T2DM models incorporating low-dose STZ alongside dietary intervention, as high-fat diet alone is not enough to induce diabetes (Barrière et al, 2018; Wanrooy et al, 2018). Notably, the use of low-dose STZ and high fat diet in a rat model replicates late-stage clinical T2DM where β-cell loss is apparent (Butler et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, among the effects of hyperglycemia seen in glial cells, It has been shown that GFAP immunoreactivity increases in the hippocampus of streptozotocin treated mice [47]. In addition, there is an increase in the numbers of GFAP + Müller cells in the retina of db/db mice as compared with non-diabetic controls [48].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the same authors concluded that HFD triggers neuroinflammation, as evaluated by reactive microglia and release of pro-inflammatory cytokines (40). Moreover, in an animal model of HFD for 9 weeks, an increase in leukocyte transmigration into the brain parenchyma was observed (41). Accordingly, in the present study we showed a downregulation of collagen IV, the most important protein of the BBB basement membrane, and the tight junction protein, claudin-5, which is strong indicator of BBB dysfunction.…”
Section: Discussionmentioning
confidence: 99%